Everyday logic about English in applied linguistic research: A topos analysis of conference abstracts on English-medium education. Issue 2 (1st October 2021) - Studer, Patrick
Abstract : This contribution analyses the argumentative premises underlying applied linguistic research conducted in the area of English-medium instruction. Applied linguistics not only studies language as it is used in the real world but is widely understood as an approach through which real-world problems in matters of language can be solved. It comes as no surprise, therefore, that applied linguistics is commonly used as a diagnostic perspective in English-medium instruction (EMI) research where it aims to provide insight into issues in need of fixing or improvement. Such studies are not conducted in an argumentative vacuum: they are embedded in a background process of policymaking, debate and discussion by stakeholders and policymakers who are involved in the introduction of English as an international language in higher education. This paper aims to highlight the argumentative backdrop against which applied linguistic research into EMI is construed and legitimised. Analysing conference abstracts in the field of EMI, the paper seeks to draw attention to everyday logic and beliefs applied linguists engage in when submitting paper proposals for conferences. It calls for a critical applied linguistic research agenda which foregrounds the potential ideological effects everyday conceptualisations of language have on EMI research and, ultimately, on EMI policymaking.